Evaluación de Relaciones entre gallinaza y agua en la producción de biogas en la granja avícola "Zambrano Ponce" del cantón Chone - Montesdeoca Zambrano, Génesis Penélope (2017)
The research was carried out at the poultry farm "Zambrano Ponce", located on the place La Estrella del cantón Chone, Province of Manabí. The objective of this research was to evaluate the relationships between gallinaza and water in biogas production. For this purpose, 9 containers were implemented in polyethylene containers, with 3 treatments and 3 replicates each, using quantities of 10, 20 and 30 Kg of chicken manure and 6 Kg of agricultural residues, with a volume of 20, 30 and 40 Lt of water respectively. After the installation of the containers, physical parameters such as temperature and pressure were monitored in all experimental units, in a period of 31 days. Average volumes generated in treatments 1, 2, and 3 were obtained with values of 7,27 m3, 13,40 m3 and 15,55 m3 respectively, being determined that the third treatment generated a larger volume of biogas. The results of the research were represented by linear regression graphs, thus reflecting that there was no greater significance among them in gas generation. Statistical analysis of the variables in the study was performed using the SPSS software, which obtained the Analysis of Variance (ANOVA), whose data showed that no significant statistical differences were found. The development of research is an environmental alternative, which transforms a large problem of pollution into a resourceful and clean resource.